1980
DOI: 10.1680/geot.1980.30.2.97
|View full text |Cite
|
Sign up to set email alerts
|

Jacked piles in London clay: interaction and group behaviour under working conditions

Abstract: This Paper describes a field investigation of the behaviour of a row of two piles and a row of three piles installed at close spacings in London Clay. It follows directly the paper by the same authors (1979) presenting observations of the shear stresses and shear strains around a single pile and the measurement techniques described in that paper have been employed and extended. The three pile row was tested under conditions of equal pile loading and equal pile displacement and also with the piles linked by a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…The measurements made by Cooke et al (1980) suggest that the interaction between piles is negligible at spacings greater than about ten pile diameters. The corner and centre piles of a 7' group at k = 2.5 would not therefore influence each other perceptibly since they are IO.6 pile diameters apart.…”
Section: Distributions Of Pile Loadingmentioning
confidence: 92%
See 3 more Smart Citations
“…The measurements made by Cooke et al (1980) suggest that the interaction between piles is negligible at spacings greater than about ten pile diameters. The corner and centre piles of a 7' group at k = 2.5 would not therefore influence each other perceptibly since they are IO.6 pile diameters apart.…”
Section: Distributions Of Pile Loadingmentioning
confidence: 92%
“…Much larger instrumented piles were tested under field conditions by Koizumi & Ito (1967) and by Cooke et al (1980). Koizumi and Ito loaded a 3' group of closed end pipe piles 300 mm dia.…”
Section: Distributions Of Pile Loadingmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, piles would transmit the entire structural load to the soft granite (SG) layer; bypassing the potentially troublesome residual soil and weathered granite layers. Validity of this assumption is supported by Butterfield and Banerjee [4] and Cooke et al [28], who have shown that the contact between raft and soil does not significantly affect the settlement of the pile group even if the load taken by the raft-soil system is as high as 50% of the total applied load.…”
Section: Fem Modelling Of Piled Raftmentioning
confidence: 97%